Creation and Ecological Crisis: A Human Predicament Discourse (Hekima Review, 2015)
In recent years, the world has experienced serious environmental challenges and dramatic disasters related to climatic change. In some regions scientic developments have also led to creation of incredible products, some of which are benecial to human life (e.g, new medicines and vaccines), while others pose possible threats to the advancement of human life on earth (e.g, biological engineering, and nuclear energy). Faced with the possible dilemmas which derive from the complexity of the above human creations and nature’s response to man’s unbridled exploitation of earth resources, we cannot sit back and do business as usual. We are called to action so as to curb the escalation of the environmental degradation and the possibilities of human self-destruction. Tis paper is one of tentative reections which analyze the areas where we as humans might have gone wrong; it seeks to put things into perspective as it suggests possible actions that could awaken our consciousnesses to help engage wholeheartedly in the preservation of the environment and protection of our ecosystem. e paper recognizes that humanity has the capacity to turn things around. It also acknowledges that humanity as co-creator has the responsibility to care, and this impels it to worry for the future and survival of the universe, hence the urgent call to action which rings louder nowadays than ever before